The techno-economic models for CR and SDN in 5G - Christos Bouras; Anastasia Kollia; Eleftheria Maligianni (12th IFIP Wireless and Mobile Networking Conference (WMNC 2019) Paris, France, 2019)
5G is closer than ever, considering that in 2020 it will have been released. Existing technologies do not adequately cover the 5G demands, therefore new or modified versions of the existing technologies should be introduced. Telecommunication operators remain skeptical about the costs induced by 5G technologies. In this context, it is fundamental that 5G enabling technologies are analyzed in a techno-economic way. In this paper, authors present models of Cognitive Radio (CR) and Software Defined Networking (SDN). They develop economic models based on the Stackelberg competition, opt for the experimentation parameters and conduct Sensitivity Analysis (SA) experiments that show which are the most influential factors for each technology proposing ways to limit them.